74‐5: Late-News Paper: High Dynamic Range Incell LCD with Excellent Performance. Issue 1 (30th May 2018) - Deng, Zhuo; Zheng, Binyi; Zheng, Jianping; Wu, Ling; Yang, Wenbin; Lin, Zongwei; Shen, Poping; Li, Junyi
Abstract : A high dynamic range LCD constituted by a 6.46 WQHD full screen with a notch was proposed, which possess mini LED local dimming technology. The fabricated HDR LCD may achieve peak brightness above 1000nits and maximum contrast over 3, 000, 000, making it a comparable display to match the performance of OLED.